A framework to analyze cerebral mean diffusivity using surface guided diffusion mapping in diffusion tensor imaging - Kwon, Oh-Hun; Park, Hyunjin; Seo, Sang Won; Na, Duk L.; Lee, Jong-Min (Frontiers in Neuroscience, 2015)
The mean diffusivity (MD) value has been used to describe microstructural properties in Diffusion Tensor Imaging (DTI) in cortical gray matter (GM). Recently, researchers have applied a cortical surface generated from the T1-weighted volume. When the DTI data are analyzed using the cortical surface, it is important to assign an accurate MD value from the volume space to the vertex of the cortical surface, considering the anatomical correspondence between the DTI and the T1-weighted image. Previous studies usually interpolated the MD value using the nearest-neighbor (NN) method or the trilinear method, even though there are geometric distortions in diffusion-weighted volumes. Here we introduce a Surface Guided Diffusion Mapping (SGDM) method to compensate for such geometric distortions. We compared our SGDM method with results using NN and trilinear methods by investigating differences in the interpolated MD value. We also interpolated the tissue classification results of non-diffusion-weighted volumes to the cortical midsurface. The CSF probability values provided by the SGDM method were lower than those produced by the NN and trilinear methods. The MD values provided by the NN and trilinear methods were significantly greater than those of the SGDM method in regions suffering from geometric distortion. These results indicate that the NN and trilinear methods assigned the MD value in the CSF region to the cortical midsurface (GM region). Our results suggest that the SGDM method is an effective way to correct such mapping errors.